2003
DOI: 10.1046/j.1471-4159.2003.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes in fetal Down syndrome brain

Abstract: Trisomy of human chromosome 21 is a major cause of mental retardation and other phenotypic abnormalities collectively known as Down syndrome. Down syndrome is associated with developmental failure followed by processes of neurodegeneration that are known to supervene later in life. Despite a widespread interest in Down syndrome, the cause of developmental failure is unclear. The brain of a child with Down syndrome develops differently from that of a normal one, although characteristic morphological differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 68 publications
4
38
0
Order By: Relevance
“…Many of the brain/neurological abnormalities associated with Down syndrome are not detected until postnatal or adult life and have not been described for Ts16 mice due to embryonic lethality (Lane et al, 1996;Engidawork and Lubec, 2003). However, the increased expression of DSCR1 and decreased NFAT activation observed in the brain of Ts16 embryos may be related to compromised cognitive function later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the brain/neurological abnormalities associated with Down syndrome are not detected until postnatal or adult life and have not been described for Ts16 mice due to embryonic lethality (Lane et al, 1996;Engidawork and Lubec, 2003). However, the increased expression of DSCR1 and decreased NFAT activation observed in the brain of Ts16 embryos may be related to compromised cognitive function later in life.…”
Section: Discussionmentioning
confidence: 99%
“…As the first manifestation of neuroanatomical abnormality, a characteristic reduced brain size of children with DS appears in the 4-to 5-month fetus and progresses during the last 3 months of gestation [9,10]. Structural MRI reports, based on fewer than 15 original studies in children and youths, have suggested that the total brain volume is smaller [11][12][13][14], with specific reductions in cerebellar [11][12][13]15] and hippocampal volumes [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The gene dosage hypothesis claims that genes encoded on chromosome 21 are expressed 1.5 times higher in DS and thus lead to the development of the DS phenotype [3,4]. However, several groups, including ours, Ferrando-Miguel/Shim/Cheon/Gimona/ Furuse/Lubec have challenged this hypothesis at the protein level [5][6][7][8][9]. It may well be that genes encoded on chromosome 21 are upregulated by a factor of 1.5 at the nucleic acid level, but no prediction about gene products, i.e.…”
Section: Introductionmentioning
confidence: 94%